Making simple robots - Ceceri, Kathy (Maker Media, 2022)
Making Simple Robots is based on the idea that anybody can build a robot! That includes kids, educators, parents, and anyone who didn't make it to engineering school. If you can cut, fold, and tape a piece of paper to make a tube or a box, you can build a no-tech robotic part. In fact, many of the models in this book are based upon real-life prototypes -- working models created in research labs and companies. What's more, if you can use the apps on your smartphone, you can quickly learn to tell robots what to do using free, online, beginner-level software like MIT's Scratch and Microsoft MakeCode. The projects in this book which teach you about electric circuits by making jumping origami frogs with eyes that light up when you get them ready to hop. You'll practice designing all-terrain robot wheel-legs with free, online Tinkercad software, and you'll create files ready for 3D printing. You'll also learn to sew -- and code -- a cyborg rag doll with a blinking electronic "eye." Each project includes step-by-step directions and clear illustrations and photographs. Along the way, you'll learn about the real research behind the DIY version, find shortcuts for making projects easier when needed, and get suggestions for adding to the challenge as your skill set grows.